Corporate Governance as a Determinant of Fraudulent Financial Statements in Banking Issuers Listed on the IDX in 2023/2024 - M. Dimas Rofiudin; Rachma Agustina (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2026)
This paper explores how internal governance frameworks influence the occurrence of balance sheet manipulations among commercial banks listed on the IDX throughout the 2023–2024 fiscal years. Given their pivotal position in maintaining economic stability and market confidence, banking institutions were prioritized for this study, despite facing substantial vulnerabilities to misconduct due to rigorous compliance demands and complex transaction processing. Drawn from the annual corporate sheets of the investigated banks, the evidence is examined within a quantitative framework. By employing specific criteria under a purposive framework, 90 firm-year data points were generated from 45 finalized sample banks out of 47 available issuers. The F-Score algorithm was employed to assess fraudulent financial statements, which served as the dependent variable in the analysis. Meanwhile, the governance metrics serve as independent variables, specifically measured through institutional stock control and board of commissioners’ autonomy. The regression path calculated via SPSS 23 demonstrates that the autonomy of the commissioners’ board exerts a significant, inverse pressure on fraudulent practices, meaning that a larger presence of outside directors helps curtail reporting misstatements. Conversely, institutional ownership does not yield any noticeable outcome. Ultimately, the tested governance dimensions operate concurrently in dictating the overall risk of financial statement falsification.